INCREASING THE POST-REPAIR DURABILITY OF HYDRAULIC PUMPS OF THE NSh-K MODIFICATION BY USING EPILAM COATINGS ON THE WORKING SURFACES OF THE PARTS - Мельянцов, Петро (SWorldJournal, 2025)
The paper considers the problem of increasing the post-repair durability of gear pumps of the NSh-K modification, which are widely used in hydraulic systems of mobile equipment. It is shown that the reduction in service life after repair is associated wi